Benefit of a multimodal approach combining chemotherapy and surgery in oligometastatic gastric cancer: experience from a tertiary referral center - Maratta, Maria Grazia; Vitale, Antonio; Basso, Michele; Vivolo, Raffaella; Di Monte, Elena; Biondi, Alberto; Di Giorgio, Andrea; Rosa, Fausto; Tondolo, Vincenzo; Agnes, Annamaria; Tortora, Giampaolo; Strippoli, Antonia; et al. (Frontiers in Oncology, 2024)
Introduction Gastric cancer (GC) is the fourth leading cause of cancer-related death worldwide with limited therapeutic options. The aim of this study was to analyze the value of adding surgery to the first-line treatment in patients with oligometastatic GC (OGC). Methods This retrospective study included patients with OGC who underwent induction chemotherapy followed by surgery of both primary tumor and synchronous metastasis between April 2012 and April 2022. Endpoints were overall survival (OS) and relapse-free survival (RFS) analyzed by the Kaplan–Meier method. Prognostic factors were assessed with the Cox model. Results Data from 39 patients were collected. All cases were referred to our multidisciplinary tumor board (MTB) to evaluate the feasibility of radical surgery. After a median follow-up of 33.6 months (mo.), median OS was 26.6 mo. (95% CI 23.8–29.4) and median RFS was 10.6 mo. (95% CI 6.3–14.8). Pathologic response according to the Mandard criteria (TRG 1–3, not reached versus 20.5 mo. for TRG 4–5; HR 0.23, p=0.019), PS ECOG ≤ 1 (26.7 mo. for PS ≤ 1 versus 11.2 mo. for PS >1; HR 0.3, p=0.022) and a low metastatic burden (26.7 mo. for single site versus 12.9 mo. for ≥2 sites; HR 0.34, p=0.039) were related to good prognosis. No major intraoperative complications nor surgery-related deaths occurred in our series. Discussion A sequential strategy of preoperative chemotherapy and radical surgical excision of both primary tumor and metastases was demonstrated to significantly improve OS and RFS. Multidisciplinary evaluation is mandatory to identify patients who could benefit from this strategy.